Exploring the Prevalence of Renewable Energy Practices and Awareness Levels in Palestine - Mai Abuhelwa; Mohamed Elnaggar; Wael A. Salah; Yasser F. Nassar; Mohammed J. K. Bashir (Energy Science & Engineering)
ABSTRACT The growing demand for energy in developing societies, coupled with dwindling conventional resources, necessitates the adoption of renewable energy (RE) sources. A comprehensive understanding of these sources and their optimal utilization is crucial. The awareness of the users plays a very important role in the effective utilization of different energy sources. Hence, this study examines the level of RE awareness in Palestine, identifying factors influencing public perception and exploring potential strategies for promoting RE adoption. This awareness depends on different factors related to the users' education level, community type, and type of building. Different factors that affect the willingness and attitude to gain knowledge about RE are presented. In addition, various practices highlighting the increasing level of awareness regarding the adoption of RE sources are investigated. In addition, the status of RE education and its potential impact on engineers have also been discussed. Various individual and institutional efforts are highlighted in the study as strategies to bridge the gap and overcome obstacles to adopting RE sources. Suggestions for better use of these resources have been highlighted. Thereafter, recommendations for effective RE implementation in Palestine are analyzed and conclusions are drawn. The main challenges in integrating RE into Palestine's existing energy grid and system include infrastructure limitations, resources and financial constraints, and political issues. Still, there are possibilities in the form of international collaboration and investment. A flexible and modular RE grid could also address some of these challenges by integrating small‐scale systems that can be scaled up as needed.